THE EFFECT OF MOTIVATOR FACTORS AND HYGIENE FACTORS ON EMPLOYEE WORK MOTIVATION - Arka'a Arka'a (LPPM STIE PERTIBA Pangkalpinang, 2018)
This study focuses on employee motivation at PT. Bumi Bangka Belitung Sejahtera. This study applies Herzberg's two-factor theory, which is trying to find the influence between motivator factor variables and hygiene factor variables on employee work motivation. This study uses quantitative methods with survey techniques, namely by using questionnaire distribution techniques. The research subjects were employees at PT. Bumi Bangka Belitung Prosperous. Processing data using multiple regression methods, to find the significance of the relationship between research variables. The results of the study were able to answer hypothesis testing, namely, there was a significance of the relationship between motivator factors and hygiene factors with employee motivation. The results of hypothesis testing indicate that there is a strong relationship between motivator factors on employee work motivation with a correlation value of 0.855 or 85.5% and the relationship of hygiene factors to employee motivation with a correlation value of 0.940 or 94.0%. The significance of the relationship proves that motivators are able to create employee satisfaction and the significance of the relationship between hygiene factors causes employees to feel less satisfied with the factors included in hygiene. The conclusion of this study proves that the better the attention to motivator factors will increase employee motivation which determines satisfaction and neglect of hygiene factors will increasingly cause employee motivation to decline and cause dissatisfaction. Attention to work motivation of employees will be able to enrich employees to develop the organization